(3YbjOI GdUQUQjs - (3GdUQUQi, CHh RcQjG, jMji Hf jhSa Hf jMji, J (B656 (3g`s ((3YHO Gddg Hf Ydj GdegjOHs)
(3ChdgG (B:s
(3HYO GdHSedI ; JhGVY dQH GdYQT dYOi JQaY dbO aGR YHOg ddegef jNaY (B- (3hOGhj HPcQ Gddg bdHc Efg cG Ydi OhGA ddbdhH hGfaYs
(3BNQgG (B:s
(3Hg GdSfI GdeKdi YQafG hCfcQJ bdhH YdjgG HGdZHGhI eWHY (B- (3Ydjg SdGe Gddg eG YGbH GdQLG UHGMG heG dGMJ HhGQb JdeYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B8 / 177s
(3eYLe GdeDdajf (B4 / 120s
(3TPQGJ GdPgH (B5 / 285s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJhMjO hGdedd hGdfMds